Access to Justice for Battered Women - Mary Becker (Washington University Journal of Law & Policy, 2003)
In this Essay, I consider some of the problems facing battered women in three situations: when involved in a custody dispute with an abuser; when on trial for the murder of an abuser or of a child killed by the abuser; and when seeking an order of protection or filing a domestic violence report with the police, thus triggering the local domestic violence response system. In my discussion of these three areas, two themes emerge. One is our systemic failure to understand the emotions of battered women, a problem often caused not by the differences between “them” and “us,” but by the similarities between their emotional responses and our own. The second is our tendency to blame the domestic violence survivor for the act of violence by seeing the consequences of domestic violence as evidence of her innate character traits, her failings, and her responsibility for violence perpetrated by someone else. Finally, I propose specific changes, including legislative action, which would improve conditions for battered women in each of the three situations discussed.
Keywords: Abused women; Access to justice; Clemency; Equal protection; Family law; United States